Factors Influencing Medication Adherence in Patients with Type 2 Diabetes Mellitus in Japan - Emira Ramadhany, Nuzla; Olivia, Viona; Putri, Nabila Azzahra; Yuwono, Brian Jordan; Oktharina, Eka Handayani; Nurwany, Raissa (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Introduction. Diabetes mellitus (DM) is a chronic metabolic disease marked by persistent hyperglicemia. Type 2 diabetes mellitus (T2DM) is increasingly prevalent in Japan, affecting approximately 10% of adults with diabetes, according to the Ministry of Health, Labor and Welfare in 2020. Maintaining medication adherence is critical for T2DM management and complications prevention. This review aimed to synthesize factors influencing medication adherence in T2DM patients in Japan. Methods. This systematic review followed PRISMA-P guidelines, using the keywords The keywords “risk factors